Metagenomic analysis reveals a rich bacterial content in high‐risk prostate tumors from African men. Issue 15 (27th August 2019) - Feng, Ye; Jaratlerdsiri, Weerachai; Patrick, Sean M.; Lyons, Ruth J.; Haynes, Anne‐Maree; Collins, Colin C.; Stricker, Phillip D.; Bornman, M.S. Riana; Hayes, Vanessa M.
Abstract: Background: Inflammation is a hallmark of prostate cancer (PCa), yet no pathogenic agent has been identified. Men from Africa are at increased risk for both aggressive prostate disease and infection. We hypothesize that pathogenic microbes may be contributing, at least in part, to high‐risk PCa presentation within Africa and in turn the observed ethnic disparity. Methods: Here we reveal through metagenomic analysis of host‐derived whole‐genome sequencing data, the microbial content within prostate tumor tissue from 22 men. What is unique about this study is that patients were separated by ethnicity, African vs European, and environments, Africa vs Australia. Results: We identified 23 common bacterial genera between the African, Australian, and Chinese prostate tumor samples, while nonbacterial microbes were notably absent. While the most abundant genera across all samples included: Escherichia, Propionibacterium, and Pseudomonas, the core prostate tumor microbiota was enriched for Proteobacteria . We observed a significant increase in the richness of the bacterial communities within the African vs Australian samples ( t  = 4.6‐5.5; P  = .0004‐.001), largely driven by eight predominant genera. Considering core human gut microbiota, African prostate tissue samples appear enriched for Escherichia and Acidovorax, with an abundance of Eubacterium associated with host tumor hypermutation. Conclusions: Our study provides suggestive evidence for the presence of a core, bacteria‐rich, prostate microbiome. While unable to exclude for fecal contamination, the observed increased bacterial content and richness within the African vs non‐African samples, together with elevated tumor mutational burden, suggests the possibility that bacterially‐driven oncogenic transformation within the prostate microenvironment may be contributing to aggressive disease presentation in Africa.